Clinical Study of Concomitant Strabismus - Sachit Mahajan1 , Satish Kumar Gupta2 (Perspectives In Medical Research, 2020)
Background and Objectives: Strabismus is a condition in which there is misalignment of visual axes of two eyes. Concomitant strabismus is a condition in which the angle of deviation is constant in all the directions of gaze. Concomitant strabismus is further classified as convergent, divergent, hyperdeviation and hypodeviation. Major presenting complaints include cosmetic blemish, diminution of vision, asthenopic symptoms like headache, eye strain and diplopia. This study was conceptualized to study the clinical and ophthalmological profile of patients with concomitant strabismus, in order to generate evidence to manage this condition more effectively. Material and Methods : This cross-sectional, observational study was conducted over a period of two years in 120 patients with concomitant strabismus. Ocular history and visual acuity were recorded. Cover, cover-uncover, alternate cover test, Hirschberg test, Krimsky test and examination by synaptophore were done. Refraction and fundus examination was also done. Result: Majority of the patients were under 5 years of age (46.6%) with male to female ratio of 2:3. Convergent squint was more common (71.6%) with majority of patients having moderate degree of deviation (58.8%). Hypermteropia was more commonly associated with squint (65%) more so with convergent squint. Eccentric fixation was present in only 10% of the cases. Conclusion: Convergent concomitant squint is more common type with majority of patients having moderate degree of deviation. Hypermetropia is more commonly associated with concomitant squint. Appropriate refraction and timely intervention can help in preventing amblyopia in young children